Antibiotic Resistance in Bacterial Pathogens - Sara M. Soto (MDPI AG, 2023)
The increasing number of infections caused by antibiotic-resistant bacterial pathogens over the last few decades has become a critical global health problem, the scale of which has led to it being named a "silent pandemic" [...]